PENGEMBANGAN MODEL ASESMEN BERBASIS STEAM UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI DAN BERPIKIR KRITIS SISWA - Utomo, Edy Setiyo; Suryowati, Eny; Chalimah, Chalimah (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Asessment has a crucial role in the learning process, especially for the students’ literacy and numeracy ability. Currently, the Indonesian students’ literacy and numeracy and critical thinking are still very low according to the data of PISA 2023. The aim of the research is to develop STEAM based assessment model, abbreviated as SLNA, to improve literacy and numeracy and critical thinking ability at junior high school level. The type of the research applies research and development (R&D) with the ADDIE model at SMPN 3 Mojokerto. The research results manifested that the expert validation had an average of 3,33 with a very valid category while practicality could be seen from the results of students’ responses of 89,5% who strongly agreed and teachers’ responses of 76% who stated that they were very practical. The effectiveness could be seen from the results of the activities, motivation, and students’ learning outcomes where the students’ motivation results were 90,7% which stated that they strongly agreed that SLNA provided motivation in learning and the average students’ learning outcomes were 82,4. The results confirm that the SLNA model is an effective assessment to support in developing students’ literacy, numeracy, and critical thinking in their learning and project practice.